Impact of FMR1 Premutation on Neurobehavior and Bioenergetics in Young Monozygotic Twins - Napoli, Eleonora; Schneider, Andrea; Hagerman, Randi; Song, Gyu; Wong, Sarah; Tassone, Flora; Giulivi, Cecilia (Frontiers in Genetics, 2018)
Mitochondrial dysfunction (MD) has been identified in lymphocytes, fibroblasts and brain samples from adults carrying a 55-200 CGG expansion in the fragile X mental retardation 1 (FMR1) gene (premutation; PM); however, limited data are available on the bioenergetics of pediatric carriers. Here we discuss a case report of three premutation carriers: two monozygotic twins (aged 8 y) harboring an FMR1 allele with 150-180 CGG repeats, with no cognitive or intellectual issues but diagnosed with depression, mood instability and ADHD, and their mother (asymptomatic carrier with 78 CGG repeats). Fibroblasts and lymphocytes from the twins presented a generalized OXPHOS deficit, altered mitochondrial network, accumulation of depolarized mitochondria, and increased mitochondrial ROS production, outcomes distinct and more severe than the mother’s ones, suggesting the involvement of modulatory effects mediated by CGG expansion, X-activation ratio, sex hormones and epigenetic factors (chronic inflammation, consequence of Lyme disease). The degree of the severity of MD appeared to segregate with the morbidity of the phenotype. The mitochondrial ROS-mediated HIF-1a stabilization was identified as a key player at contributing to the mitochondrial dysfunction, pointing it as a novel target for future therapeutical intervention.